Resinas compuestas precalentadas como agente de cementación. Revisión bibliográfica - Salinas Valverde, Katty Lizbeth (2024)
Preheated composite resins are used as a cementation agent for indirect restorations, achieved by preheating the conventional composite resin, which consists of increasing its temperature prior to its application using devices specifically designed for this purpose. In order to explore the subject in more depth, a literature review was carried out with the aim of analysing preheated composite resins as a luting agent. For this purpose, 23 scientific articles were considered, which were compiled by searching with key words in the following scientific databases: Pubmed, Scopus, Google Scholar and Scielo, with a maximum age range of 10 years. The results showed that the composite resin heater Calset (AdDent) was the most used by 36.76%, at a temperature of 68°C, and, in times mostly reported from 0 to 9 minutes, it was identified that the most used type of resin was microhybrid resin. Furthermore, it was evident that the preheated composite resin showed great versatility when applied as a cementation agent to indirect restorations such as feldspar and lithium disilicate veneers, lithium disilicate crowns and resin inlays. Among the most frequently observed advantages were increased microhardness and reduced viscosity (28.57%), while the most frequent disadvantage (60%) was increased film thickness. From this, it was concluded that preheated composite resins are a good alternative as a cementation agent for indirect restorations by reducing their viscosity and increasing their microhardness